Increased IL-15 Production and Accumulation of Highly Differentiated CD8+ Effector/Memory T Cells in the Bone Marrow of Persons with Cytomegalovirus - Pangrazzi, Luca; Naismith, Erin; Meryk, Andreas; Keller, Michael; Jenewein, Brigitte; Trieb, Klemens; Grubeck-Loebenstein, Beatrix (Frontiers in Immunology, 2017)
Cytomegalovirus (CMV) has been described as a contributor to immunosenescence, thus exacerbating age-related diseases. In persons with latent CMV infection, the CD8+ T cell compartment is irreversibly changed, leading to the accumulation of highly differentiated virus-specific CD8+ T cells in the peripheral blood. The bone marrow (BM) has been shown to play a major role in the long-term survival of antigen-experienced T cells. Effector CD8+ T cells are preferentially maintained by the cytokine IL-15, the expression of which increases in old age. However, the impact of CMV on the phenotype of effector CD8+ T cells and on the production of T cell survival molecules in the BM is not yet known. We now show, using BM samples obtained from persons who underwent hip replacement surgery because of osteoarthrosis, that senescent CD8+ TEMRA cells with a bright expression of CD45RA and a high responsiveness to IL-15 accumulate in the BM of CMV-infected persons. A negative correlation was found between CMV antibody (Ab) titers in the serum and the expression of CD28 and IL-7Rα in CD8+ TEMRAbright cells. Increased IL-15 mRNA levels were observed in the BM of CMV+ compared to CMV- persons, being particularly high in old seropositive individuals. In summary, our results indicate that a BM environment rich in IL-15 may play an important role in the maintenance of highly differentiated CD8+ T cells generated after CMV infection.